IMPLEMENTASI KEBIJAKAN BANTUAN PENDIDIKAN KURANG MAMPU DI BIRO ADMINISTRASI KESEJAHTERAAN RAKYAT SEKRETARIAT DAERAH PROVINSI RIAU TAHUN 2017 - Iqbal, Said Muhammad; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Educational support for poor people was a donation for poor society which taken from provincial government budget for avoiding a probable social risks. Administration Bureau of Social Welfare of Riau Province that handled the administation affairs of the educational support for poor people faced some problems of implementing the policy. They were the process of implementing and long time of money cashing. The concept of influencing factor used Warwic in Tahir (2015). In this policy impelementaion, there were some factors should be attended, such as 1) organization capability; 2) information; 3) support 4) pontential allotment. For getting the informant, this research used purposive sampling. The data wereobtained from two sources. The primary sources were from the interview and the result of observation. The secondary data were from book, document, and data from Local Secretariate of Riau Province. The result of the research showed that many factors influenced the policy implementation of educational support for poor people at Administration Bureau of Social Welfare in Local Secretariate of Riau Province. They were the problems of local budget, responsibility, and human resources.Keywords: Implementation, Policy, Educational Support.